(untitled) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2015)
The paper theoretically grounded pedagogical conditions that ensure a positive impact of personality-oriented approach. Determined the essential characteristics of the professional competence of future teachers of the Ukrainian language. The attention to psychological factors, pedagogy effect on activation of creative and cognitive abilities of students-philologists. Presented by the author’s vision of the main components of the formation of a holistic professional.